2017
DOI: 10.7241/ourd.20174.111
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of patch test reactivity among patients with clinical diagnosis of contact dermatitis: A hospital-based study

Abstract: Introduction:The patterns of positive patch test in Nepal have not been defined so far. The aim of this study was to describe the patterns of patch test reactivity in suspected Allergic Contact Dermatitis (ACD) patients. Methods: This was a hospital based retrospective study performed to investigate patch test reactivity in patients with ACD from April, 2016 through October, 2016. The data of patients who underwent patch test during this period were extracted and analyzed. Results: A total of 35 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 6 publications
4
8
0
Order By: Relevance
“…Similarly, some studies got even higher sensi za on than noted by Parajuli et al; Sharma VK et al 1998 (65.5%) and VK Sharma et al 2004 (63.6%). 5,9,10 The most common pa ern was the hand eczemas, which was similar to the fi ndings of Parajuli et al (2017), Agrup G 1969, Goh C L 1989 and Holness D L et al 1995. 5,[11][12][13] This was in contrast to Indian studies which showed air borne contact derma s as being the commonest type of eczema.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Similarly, some studies got even higher sensi za on than noted by Parajuli et al; Sharma VK et al 1998 (65.5%) and VK Sharma et al 2004 (63.6%). 5,9,10 The most common pa ern was the hand eczemas, which was similar to the fi ndings of Parajuli et al (2017), Agrup G 1969, Goh C L 1989 and Holness D L et al 1995. 5,[11][12][13] This was in contrast to Indian studies which showed air borne contact derma s as being the commonest type of eczema.…”
Section: Discussionsupporting
confidence: 86%
“…7,8 But contrary fi nding was found in study conducted in Nepal by Parajuli et al (2017) which showed a higher allergic reac on (54.3%). 5 The discrepancy might be due to their small sample size (35 pa ents). Similarly, some studies got even higher sensi za on than noted by Parajuli et al; Sharma VK et al 1998 (65.5%) and VK Sharma et al 2004 (63.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of the cases it is not possible to identify the cause as irritant or allergic. So, patch testing becomes an important diagnostic tool for identification of the allergen or allergens responsible for eczema [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Fragrances are found in many cosmetics, as well as more traditionally in perfume or cologne form. Fragrances, including fragrance mix, balsam of Peru, and cinnamic aldehyde are the most commonly identified allergens in cosmetic-induced ACD [2,3].…”
Section: Introductionmentioning
confidence: 99%